A UPnP-based Decentralized Service Discovery Improved Algorithm - Yu Shi-cai; Wu Yan-zhi; Guo Run-niu (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
The current UPnP service discovery algorithm in the presence of the service can cause severe drops in the digital home network. The reason is that the root devices instantly send delay sending response messages and randomly selected independent response message congestion through simulation analysis. To solve these problems, an improved UPnP service discovery algorithm was given. Considering the length of the message and the bandwidth of the router, derived by testing the router the packet loss rate can be reduced